Reversible gasochromic hydrogen sensing of mixed-phase MoO3 with multi-layered Pt/Ni/Pt catalyst - Han, Seung Ik; Lee, Sang Yeon; Duy, Le Thai; Seo, Hyungtak (International Journal of Hydrogen Energy, 2021)
Visual detection of hydrogen is important for hydrogen-powered vehicles and hydrogen fuel stations. However, there are few studies on such the sensing approach, particularly solving challenges about the endurance or reusability of the sensors. Here, our development of superior reversible gasochromic hydrogen sensors based on a novel combination of a multi-layered Pt–Ni catalyst and a mixed-phase MoO3 active layer is introduced. The mixed α and β phases in the MoO3 layer can provide more high-energy sites for gasochromic reactions. The Pt–Ni catalyst, where Ni serves as a modifier of surface atoms’ diffusivity, successfully converts the mostly irreversible gasochromic sensing mode of MoO3 to the reversible gasochromic mode. Our hydrogen sensor shows coloration from grey to navy blue within 30 s, and its recovery occurs within 50 s. Furthermore, it can detect H2 gas (5–1000 ppm) in both optical and electrical modes. Notably, our sensor is all constructed through dry processes, raising its potential for large-scale manufacture and integration.
Keywords: Gasochromic; Hydrogen sensor; Hydrogen-sensing; Mixed phase; MoO$-3$; Multi-layered; Multi-layers; Pt-Ni catalysts; Pt–ni; Reversible; Gasochromic; Hydrogen sensor; MoO3; Multi-layer; Pt–Ni; Reversible